1951
DOI: 10.1136/jnnp.14.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Disability Caused by Brain Wounds: A Review of 1,166 Cases

Abstract: This paper is based on a follow-up study which has continued throughout and since the late war. The study centres around the work done by many specialists at the Military Hospital for Head Injuries, Oxford, and with the mobile neurosurgical units in different theatres of war. The Medical Research Council has assisted throughout in providing for the preservation and copying of case records, and since the war, with aid from the Nuffield Provincial Hospitals Trust, it has been possible to organize a small Head In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1952
1952
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…In contrast, in the total group of over 200 men who have attended for follow-up in the Oxford study, there has been one suicide and one attempted suicide. In his earlier 5-year follow-up of 1,166 cases, Russell (1951) reported two deaths from suicide.…”
Section: Psychological Outcomementioning
confidence: 96%
“…In contrast, in the total group of over 200 men who have attended for follow-up in the Oxford study, there has been one suicide and one attempted suicide. In his earlier 5-year follow-up of 1,166 cases, Russell (1951) reported two deaths from suicide.…”
Section: Psychological Outcomementioning
confidence: 96%
“…So far as the general distribution of wounds is concerned, in this series one of us (Russell, 1947) has previously suggested that injury to inhibitory (suppressor) areas might be especially epileptogenic, since this might result in a removal of some degree of normal inhibition from all areas with neuronal 97 by copyright. connexions from the damaged area.…”
Section: )mentioning
confidence: 99%
“…These will be studied in their varying forms in a later section. One of us (Russell, 1951) in a preliminary reference to some of these figures has drawn attention to the tendency for a one-toone ratio to develop between the total numbers of cases of brain wound which do and do not develop fits. Further, Penfield (1952) refers to the cure-rate of traumatic epilepsy by operative excision of a brain scar or focus as about the same (50%).…”
Section: )mentioning
confidence: 99%
“…3 Other PHI studies have found an association between frontal and temporal lesions and PTE. 36,37 Conversely, one study of CHI and PHI found no correlation between lesion site and PTE. 38 There have been reports of an increased incidence of later-onset PTE in those with bilateral parietal lesions, suggesting a possible timedependent process occurring in certain subtypes of PTE.…”
Section: Associations With Intelligencementioning
confidence: 99%